Third-order method for simulation of compressible flows - Wieteska, R.; Rokicki, J. (Archives of Mechanics, 2008)
The paper discusses finite volume WENO reconstruction applied to simulation of compressible 3D Euler flows. The main objective of this work is presentation of the new reconstruction procedure (third-order of accuracy in space), together with the procedure for integration of numerical fluxes applied to simulations of compressible 3D Euler flows, using unstructured meshes.